The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1007/s00774-016-0739-x
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D-binding protein, vitamin D status and serum bioavailable 25(OH)D of young Asian Indian males working in outdoor and indoor environments

Abstract: Urban Asian Indians generally have low serum 25(OH)D. Information on serum bioavailable 25(OH)D and the effect of prolonged sun-exposure in them is not known. We assessed serum 25(OH)D and bioavailable 25(OH)D in males with varying durations of sun-exposure in Delhi during August-September. Serum 25(OH)D, vitamin D-binding protein (DBP), bioavailable 25(OH)D, free 25(OH)D index, iPTH, ionized calcium and sun-index were assessed in outdoor, mixed outdoor-indoor and indoor workers (n = 88, 32 and 74, respectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 30 publications
3
26
2
Order By: Relevance
“…The examples include farmers of Nebraska, coastal guards, field workers in Florida, and countries with plenty sunshine as Hawaii, Israel and Australia, where serum 25(OH)D ranged from 75 to 160 nmol/L . The vitamin D status of traditional hunters in Tanzanian, Caribbeans and Indian construction workers too ranged from 75 to 115 nmol/L …”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…The examples include farmers of Nebraska, coastal guards, field workers in Florida, and countries with plenty sunshine as Hawaii, Israel and Australia, where serum 25(OH)D ranged from 75 to 160 nmol/L . The vitamin D status of traditional hunters in Tanzanian, Caribbeans and Indian construction workers too ranged from 75 to 115 nmol/L …”
Section: Discussioncontrasting
confidence: 73%
“…Interestingly, our recent study showed normal vitamin D status in outdoor construction workers of Delhi . Absence of VDD in the construction workers was explained by compulsory long hours of sun exposure.…”
Section: Introductionmentioning
confidence: 99%
“…A recent observational study on adult Indians has documented that sunshine exposure is associated with higher serum 25(OH)D levels [9]. Outdoor manual workers in Delhi had normal vitamin D status with mean serum 25(OH)D values between 20 and 30 ng/mL [9].…”
Section: Vitamin D Sufficiency Through Sunshine Inmentioning
confidence: 99%
“…Outdoor manual workers in Delhi had normal vitamin D status with mean serum 25(OH)D values between 20 and 30 ng/mL [9]. It is possible that the lack of adequate sunshine exposure among mothers and their offspring is resulting in a high prevalence of biochemical vitamin D deficiency.…”
Section: Vitamin D Sufficiency Through Sunshine Inmentioning
confidence: 99%
“…In another study from north India,[4] authors compared serum 25(OH) D and bioavailable 25(OH) D in males with varying durations of sun-exposure between indoor and outdoor environments in Delhi during August–September. They demonstrated that serum 25(OH)D increases by 2.03 ng/mL per hour of sun-exposure (95% confidence interval 1.77–2.28; P < 0.001).…”
mentioning
confidence: 99%